The Role of Religiousness on Substance-Use Disorder Treatment Outcomes: A Comparison of Black and White Adolescents - Krentzman, Amy R. (2012)
This study compares 41 Black and 124 White adolescents at intake and discharge from a residential treatment program for substance-use disorders. Study data were obtained as part of a larger study (N = 195) that sought to assess the relationship of helping behavior and addiction recovery. This post-hoc analysis aims to identify cultural strengths that may be associated with recovery from substance-use disorders among Black adolescents. Using regression analyses and controlling for the severity of substance use and background variables that distinguish racial groups, religious practices and behaviors at intake were examined. Specifically, Black youth and White youth were compared on treatment outcomes, including alcohol or drug use during treatment, drug craving, 12-Step work, and 12-Step helping. The burden of health and socioeconomic disparities at intake did not disproportionately disfavor Black adolescents. Outcomes related to 12-Step measures were similar between Black and White youth. White adolescents reported higher craving scores at discharge, and Black adolescents were more likely to use drugs during treatment. High levels of religiousness at treatment intake were linked to greater 12-Step work and greater 12-Step helping at discharge. High levels of religiousness at intake were not related to drug use during treatment or to craving scores at discharge. The relationship between intake levels of religiousness and treatment-related outcomes did not differ by race.